VISUALISASI TOKOH RAJA HAYAM WURUK DAN MAHAPATIH GAJAH MADA DALAM BENTUK DESAIN KARAKTER DI ERA DIGITAL 4.0 DALAM BENTUK DRAFT E-BOOK - Rafiansyah, Azhario Thoriq (Fakultas Ilmu Budaya, Universitas Brawijaya, 2023)
Today, precisely in the digital era 4.0, there are many uses of digital media that are used for daily activities, one of which is making visual works through digital media assisted by computers, drawing tablets, and applications made specifically to create works. Many people in Indonesia, especially young people, are interested in drawing using this digital media. Some use their work to make money and some work to find their existence on social media, unfortunately it is still rare to find elements of local history that are raised through the works made by them. Therefore, in this creation, it is necessary to introduce how the concepts and ideas of the figures of king Hayam Wuruk and mahapatih Gajah Mada are equipped with visualizations so that elements of local history can be raised through works made by young people. The purpose of this creation is to provide a visual reference for young people about one of the history that has ever existed in Indonesia, namely the existence of the Majapahit kingdom which reached its glory under the reign of King Hayam Wuruk with his mahapatih Gajah Mada who was famous for his palapa oath.The method used in making the work is the Hawkins method. The Hawkins method was chosen because the author re-describes existing characters by improvising some parts of the visualized characters. In its creation, the work is made in the form of character designs because a character design is able to display an attractive visualization so that it can be more easily remembered by the public, especially young people. Although the two figures of the Majapahit kingdom can be visualized through their characteristics, further research is still needed on what the original figures of Hayam Wuruk and Gajah Mada were like.